Pesticides in water sources used for human consumption in the semiarid region of Argentina - Mas, Laura Ines; Aparicio, Virginia Carolina; De Geronimo, Eduardo; Costa, José Luis (Springer, 2020)
Presence of pesticides in drinking water is an issue of great concern in agricultural areas. In Argentina’s semiarid regions, where surface water sources are scarce and groundwater may be of poor quality, rainwater becomes important for safe water supply. The expansion of agriculture in these regions due to no till management has led to a high use of pesticides which jeopardize the safety of all water sources used for human consumption. The objective was to monitor the presence of pesticides in different water sources from two agricultural areas of Santiago del Estero. Samples belonged to cisterns in which rainwater is collected, wells and dams. The most contaminated sources were dams, followed by cisterns and wells. Applied doses and frequency of use played an important role in the presence of pesticides. Thus, the most frequent molecules were mainly herbicides; atrazine and metolachlor were the most abundant. Glyphosate and aminomethylphosphonic acid presented the highest concentrations. Almost all measured values were below the US Environmental Protection Agency limits, but 73% of the samples exceeded the limit of 0.5 μg L−1 established by the European Union for the sum of molecules although only 7.4% of individual molecules exceeded the limit of 0.1 μg L−1. However, risk assessment showed that pesticides from all sources presented a low potential risk to human health through drinking water exposure route.